VIDEO ANIMASI SEBAGAI MEDIA PENYULUHAN DAPAT MENINGKATKAN PENGETAHUAN DAN SIKAP REMAJA TENTANG BAHAYA FAST FOOD - Al Rahmad, Agus Hendra; Annisa, Siti Fainurryzky (Media Penelitian dan Pengembangan Kesehatan, 2025)
Nutritional problems in adolescents are due to poor nutritional intake, which results in an imbalance between intake and needs. The Western diet in adolescents is increasing, one of which is the frequent consumption of fast food. Counseling about the dangers of fast food using print media is less effective, so the use of animated videos is more likely to be utilized as a medium for counseling. The study aimed to measure the benefits of nutrition counseling using animated video media on knowledge and attitudes in adolescents about the dangers of fast food. The research used a quasi-experimental design, which was conducted on adolescents of SMA Negeri 3 Banda Aceh (Senior High School) from January to March 2023. The sample consisted of 40 adolescents in class XI, selected by purposive sampling. Data were collected through an interview using questionnaire, both before and after the intervention. The intervention was conducted through counseling using animated video media on the dangers of fast food. Data analysis was performed using Paired T-test at 95% CI. The result showed there was an increase in knowledge from (59.00) to (87.00) and an increase in attitude from (64.74) to (80.01) about the dangers of fast food. There is an effect of counseling using animated video media on increasing knowledge (p=0.001) and attitude (p=0.019) of adolescents about the dangers of fast food. In conclusion, the use of animated videos as  medium for counseling has significant benefits in increasing adolescents' knowledge and attitudes about the dangers of fast food consumption.